Multiple diffusion pathways in LixNi0.77Co0.14Al0.09O2 (NCA) Li-ion battery cathodes. Issue 23 (28th May 2020) - Ashton, Thomas E.; Baker, Peter J.; Bauer, Dustin; Groves, Alexandra R.; Sotelo-Vazquez, Carlos; Kamiyama, Takashi; Matsukawa, Takeshi; Kojima, Kenji M.; Darr, Jawwad A.
Abstract : Experimental evidence for the presence of two diffusion pathways, namely the oxygen dumbbell hop (ODH) and tetrahedral site hop (TSH), has been given for the first time by muon spin relaxation (µSR) in layered oxide lithium ion battery cathodes. Abstract : Experimental evidence for the presence of two computationally theorised diffusion pathways, namely the oxygen dumbbell hop (ODH) and tetrahedral site hop (TSH), has been given for the first time by muon spin relaxation (µSR) on sub-stoichiometric Li x Ni0.77 Co0.14 Al0.09 O2 . µSR has proven to be a powerful tool that is able to discriminate between diffusion pathways that occur on different timescales on a local level, where bulk electrochemical techniques cannot. Whereas the estimated values of D Li at lithium concentrations of 0.87 and 0.71 were found to be on the order of 10 −11 by electrochemical impedance spectroscopy, contributions to diffusion from ODH and TSH were determined to be on the order of 10 −11 and 10 −10 cm 2 s −1, and a factor of four decrease in E a for both samples, in excellent agreement with theoretical calculations on related compounds. Rietveld refinement of both X-ray and neutron diffraction data was also used to interrogate the local structure of the materials where no contribution from Li + /Ni 2+ cation mixing was observed.